Both protein kinase G dependent and independent mechanisms are involved in the modulation of glutamate release by nitric oxide in rat hippocampal nerve terminals - Sequeira, Sónia M. (1999)
We compared the effects of sodium nitroprusside (SNP), and of 8-bromo guanosine 3',5'-cyclic monophosphate (8-BrcGMP), on the 4-aminopyridine (4-AP)-evoked Ca2+-dependent release of glutamate from hippocampal nerve terminals and further investigated the role of protein kinase G (PKG) in this mechanism. SNP and 8-BrcGMP dose-dependently inhibited glutamate release, however SNP concentrations ([SNP])>500 [mu]M abolished the 4-AP evoked release, whereas 8-BrcGMP maximally inhibited the release by about 30%. The inhibition of glutamate release at low concentrations of SNP (<=5 [mu]M) was of about 20%, and was reversed by Rp-8(4-chlorophenylthio)guanosine-3',5'-cyclic-monophosphorotioate) (RpCPTcGMP, 50 nM), but the inhibition at higher concentrations (5<SNP<=50 [mu]M) was insensitive to the PKG inhibitor, but sensitive to [1H-(1,2,4)oxadiazolo(4,3-a)quinoxalin-1-one] (ODQ), which partially prevented the inhibition. [SNP]>50 [mu]M strongly inhibited glutamate release, and this was not reversed by either inhibitor. Furthermore, [SNP]<=50 [mu]M enhanced cGMP formation, and the observed effects were not related to either decreased Ca2+ entry or ATP/ADP levels. Our results indicate that NO/PKG is the signaling pathway underlying the inhibition of glutamate release at low concentrations of NO, and imply that other NO-dependent, but PKG-independent, mechanisms are activated and have complementary roles at higher NO concentrations.